PENGARUH KURIKULUM MERDEKA DAN KREATIVITAS TERHADAP KOMPETENSI GURU DI SD NEGERI SEKECAMATAN SEWON - Arif Eka Prabawa; Septian Aji Permana; Andayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the Independent Curriculum and teacher creativity on the competence of elementary school teachers in Sewon District. The research method used was quantitative with a descriptive-correlative approach. The population consisted of 220 public elementary school teachers, with a sample of 142 respondents selected using proportional random sampling. Data collection employed questionnaires on Independent Curriculum implementation, teacher creativity, and teacher competence. Instrument validity was tested using Pearson’s product-moment correlation, while reliability was tested using Cronbach’s Alpha. Data analysis applied multiple linear regression. The results revealed that: (1) the Independent Curriculum significantly influenced teacher competence (t = 11.030; sig. 0.000 < 0.05); (2) teacher creativity significantly influenced teacher competence (t = 4.460; sig. 0.000 < 0.05); and (3) both the Independent Curriculum and teacher creativity simultaneously had a significant positive effect on teacher competence (F = 306.568; sig. 0.000 < 0.05), contributing 81.5%. These findings indicate that enhancing teacher competence requires consistent implementation of the Independent Curriculum along with continuous development of teacher creativity in teaching practices.